Enteroadherent Escherichia coli as a cause of diarrhea among children in Mexico. - Mathewson, J J (1987)
Enteropathogenic Escherichia coli (EPEC) often exhibits localized adherence or diffuse adherence to HEp-2 cells. We recently provided evidence that HEp-2 cell-adherent or enteroadherent E. coli (EAEC) not belonging to EPEC serogroups was the cause of diarrhea among U.S. travelers to Mexico. In the present study, we looked for EAEC and EPEC in stool specimens from 154 children with acute diarrhea and 137 well children seen at several outpatient clinics in Guadalajara, Mexico. EAEC showing localized adherence (EAEC-L) was isolated from 13.0% of the patients and 0.7% of the controls (P less than 0.0001). EAEC showing diffuse adherence (EAEC-D) was recovered from 20.8% of the patients and 7.3% of the controls (P less than 0.001). EPEC was isolated from 4.5 and 6.7% of the patients and controls, respectively. Among all enteropathogens, only enterotoxigenic E. coli occurred as commonly (21.4%) as EAEC-D and EAEC-L did in children with diarrhea. Of the EAEC-L strains isolated from children with diarrhea, 20% belonged to recognized EPEC serogroups, and 3.1% of EAEC-D strains belonged to recognized EPEC serogroups. This study suggests that EAEC may be an important pediatric enteropathogen in Mexican children with diarrhea and further supports the observation that adherence to HEp-2 cells may be a marker of virulence independent of EPEC serogroup among E. coli strains.